A study of essential oils' medicinal uses and connection to dentistry: A review (International Journal of Food and Nutritional Sciences, 2022)
There are a number of side effects associated with current antibacterial therapies, and bacterial resistance to the antibiotics is also rising. Therefore, there is a need to identify superior substitutes. Since the beginning of time, essential oils (EOs) have been utilized to cure a variety of diseases and have grown in popularity. Numerous clinical investigations have demonstrated the safety and effectiveness of EOs. This article provides a general summary of EOs, their applications, and unfavorable effects. The PubMed database was searched for clinical trial studies and reviews on EOs that had been published up until 2020. "Lavender essential oil," "cinnamon oil," "clove oil," "eucalyptus oil," "peppermint oil," "lemon EOs," and "tea tree oil" were utilized as search terms. Total of 60 pertinent articles were discovered in the PubMed database. 42 publications were chosen to be included in the present evaluation after abstracts were reviewed. Based on the information now available, it can be said that EOs have the potential to be developed as therapeutic or preventive medicines for a variety of oral disorders, but additional clinical trials are needed to confirm their safety and efficacy.